Acinar cell carcinomas of the pancreas: a molecular analysis in a series of 57 cases - Bergmann, Frank; Aulmann, Sebastian; Kloor, Matthias; Hartwig, Werner; Moldenhauer, Gerhard; Capper, David; Dyckhoff, Gerhard; Freier, Kolja; Herpel, Esther; Schirmacher, Peter; Mechtersheimer, Gunhild (Virchows Archiv, 2014)
Pancreatic acinar cell carcinomas (PACs) are rare but are distinct aggressive neoplasms that phenotypically differ from pancreatic ductal adenocarcinomas (PDACs) and pancreatic neuroendocrine neoplasms (PNENs). Despite recent work on the genetic changes of PACs, their molecular pathogenesis is still poorly understood. In this study, we focus on a comparative genomic hybridization analysis. Based on frequent chromosomal imbalances, the involvement of DCC and c-MYC in the pathogenesis of PACs is further investigated. Moreover, we examine markers harboring potential therapeutic relevance (K-RAS, BRAF, EGFR, MGMT, HSP90, L1CAM, Her2). PACs revealed a microsatellite stable, chromosomal unstable genotype, defined by recurrent chromosomal losses of 1p, 3p, 4q, 5q, 6q, 8p, 9p, 11q, 13q, 16q, and 18, as well as gains of 1q, 7, 8q, 12, 17q, and 20q. Subsets of PAC displayed reduction/loss of DCC (79 %) and c-MYC-amplification (17 %). Significant EGFR expression occurred in 42 %, HSP90 expression in 98 %, L1CAM expression in 72 %, and loss of MGMT in 26 %. Two cases carried a K-RAS mutation. Mutations of EGFR or BRAF were not detected. All cases were Her2/neu-negative. PACs display characteristic chromosomal imbalances which are distinctly different from those in pancreatic ductal adenocarcinomas and pancreatic neuroendocrine neoplasms. Our findings suggest that DCC and c-MYC alterations may play an important role in the pathogenesis of PACs. Furthermore, EGFR, MGMT, HSP90, and L1CAM may be useful as therapeutic markers and predictors of response to therapy in a subset of PACs.
Gesehen am 14.10.2020